PERILAKU PETANI DALAM PENGELOLAAN USAHATANI KELAPA DI DESA GOSOMA KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA - Paulus H. Tobelo; Esry O.H. Laoh; Jean F.J. Timban; Jenny Baroleh (Universitas Sam Ratulangi, 2015)
ABSTRACT This study aims to identify the behavior of farmers in managing coconut farm in the village of Gosoma, Tobelo district. Coconut farming in this area is not something new for the community, since it has been done using conventional practices revealing their penetration in the culture in this place. This culture should be adjusted to the farmers’ economic needs. This can be a barrier if farmers have limited knowledge and their attitudes are still very traditional. This research was conducted in the Gosoma village, Tobelo District. Data were collected for three months, from August to October 2014. The data obtained are primary data and secondary data. Primary data were obtained directly from a survey for farmers involved in managing coconut farming in the village of Gosoma. The secondary data were obtained from some government bodies related to this study. The author takes a sample using purposive sampling technique with sample size of 50% of the total population or 60 coconut farmers. The results show that 1) Farmers still apply traditional coconut processing, and still have the tendency to maintain the heritage. 2) Coconut farmers like coconut farming jobs because they are used to working as farmers. There are a few who do not like to be farmers because of occasionally insufficient income in this business. Until now the coconut farmers have not been formally trained, but have learned from practices shown by their ancestors. They were able to maintain their plantations because of the finances they get from this business. 3) Almost all parts of the coconut tree can be used such as midrib, leaves and shells. However, the processing or utilization of the waste of palm trees has not been optimally processed. Some people argued that the waste is useless and worthless. The conclusions of the study are 1) The farmers in the village of Gosoma still apply traditional ways in managing coconut farm. There are four reasons behind this. Firstly, out of the 60 coconut farmer respondents in the village of Gosoma, there are only 15% who are actively doing family run coconut farming. Secondly, most the the 60 farmer respondents still rely on the products of their coconut farm. Moreover, for the coconut farmer, agricultural land is everything that makes a reliable source of food, a highly valued property, and the most important factor for social status. Thirdly, out of the 60 farmer respondents there are 45 respondents who have a very strong will to preserve tradition and social solidarity. Coconut farming waste is used for food and other daily needs. Coconut tree trunks and palm fronds are used as firewoods in the kitchen. Coconut fiber and shell are usually sold. The coconut shell is sometimes used to heat traditional iron to press clothes. Key words: farmers’ behavior, managing coconut farm, Tobelo